Fatalism and educational disparities in beliefs about the curability of advanced cancer. Issue 1 (January 2018) - Duberstein, Paul R.; Chen, Michael; Chapman, Benjamin P.; Hoerger, Michael; Saeed, Fahad; Guancial, Elizabeth; Mack, Jennifer W.
Highlights: Many patients with advanced cancer believe that they can be cured. These beliefs are more common in people without a high school education, and can be ascribed to their greater levels of fatalism. Interventions are needed to help oncologists care for patients with advanced disease who hold fatalistic beliefs. Abstract: Objective: Understanding socioeconomic disparities in the care of patients with incurable cancer is a high priority. We hypothesized that patients without a high school education are more likely to believe that they could be cured and we explored the role of fatalism. Methods: We studied 977 patients with advanced, incurable cancer. Two logistic regression analyses were conducted. Model One examined the effect of education on beliefs about curability. Model Two added fatalism. Results: The significant association between having less than a high school education and the belief that advanced cancer can be cured (OR = 2.55; 95% CI: 1.09–5.96) in Model One was attenuated by 39% and rendered nonsignificant in Model Two. Fatalism was associated with the belief that advanced cancer can be cured. Whites were less likely to believe they could be cured than Blacks and Asians/Pacific Islanders. Beliefs about curability were not associated with income or insurance status. Conclusions: People who do not complete high school are more likely to believe that their advanced cancer is curable, in part because they are more likely to hold fatalistic worldviews. Practice implications: Interventions to help oncologists care for patients with fatalistic beliefs could mitigate socioeconomic disparities in end-of-life care.